2018
DOI: 10.3390/molecules23112906
|View full text |Cite
|
Sign up to set email alerts
|

Co-Delivery of Gemcitabine and Paclitaxel in cRGD-Modified Long Circulating Nanoparticles with Asymmetric Lipid Layers for Breast Cancer Treatment

Abstract: Combination chemotherapy is a common clinical practice in cancer treatment. Here, cyclic RGD (arginylglycylaspartic acid) peptide was introduced to the surface of lipid/calcium/phosphate (LCP) asymmetric lipid layer nanoparticles for the co-delivery of paclitaxel (PTX) and gemcitabine monophosphate (GMP) (P/G-NPs). The sphere-like morphology of P/G-NPs displays a well-distributed particle size, and high entrapment efficiency and drug loading for both PTX and GMP, with a positive zeta potential. P/G-NPs were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…While the exact mechanisms leading to this enhanced therapeutic index is not clear, it is likely through enhancement in differential drug distribution and pharmacokinetic profile. With two drugs in one intravenous injection, the DcNP formulation has prolonged the apparent elimination half-life of gemcitabine by more than 8× and enhanced its AUC by nearly 60×, higher than known previous achievements [17,18]. Such enhancement may owe to association to DcNP, together with reduced paclitaxel clearance; plus potentially prevent exposure of DcNP bound gemcitabine inactivation by cytidine deaminase (to 2',2'-difluorodeoxyuridine, or dFdU) in liver and cells [19].…”
Section: Discussionmentioning
confidence: 94%
“…While the exact mechanisms leading to this enhanced therapeutic index is not clear, it is likely through enhancement in differential drug distribution and pharmacokinetic profile. With two drugs in one intravenous injection, the DcNP formulation has prolonged the apparent elimination half-life of gemcitabine by more than 8× and enhanced its AUC by nearly 60×, higher than known previous achievements [17,18]. Such enhancement may owe to association to DcNP, together with reduced paclitaxel clearance; plus potentially prevent exposure of DcNP bound gemcitabine inactivation by cytidine deaminase (to 2',2'-difluorodeoxyuridine, or dFdU) in liver and cells [19].…”
Section: Discussionmentioning
confidence: 94%
“…In order to further observe the cellular uptake of GX1modified nanoparticles on MKN45 and Co-HUVEC cells, NLCs containing 6C instead of PTX were prepared. 51 The results showed that the uptake rates of the PTX and the two NLCs by Co-HUVEC cells were in the order of GX1-6C-NLCs > 6C-NLCs > free 6C, while the GX1-6C-NLCs and 6C-NLCs had no significant difference uptake effect on MKN45. The results of the cellular uptake study were consistent with those from the CCK8 assay, indicating that GX1 can increase the selective adsorption ability of nanoparticles to Co-HUVEC cells.…”
Section: Discussionmentioning
confidence: 89%
“…This resulted in reduction of lung and liver metastasis of breast cancer in vivo [ 134 ]. RGD peptide functionalized NPs can be a useful tool to delivery chemotherapy drugs, such as Doxorubicin (DOX) and Paclitaxel (PTX) [ 141 , 142 ]. Figure 4 B illustrates cancer cells targeting achieved by active drug delivery mechanisms [ 25 ].…”
Section: Nanotherapeuticsmentioning
confidence: 99%